2021
DOI: 10.1039/d0dt04261g
|View full text |Cite
|
Sign up to set email alerts
|

A chromatography-free total synthesis of a ferrocene-containing dendrimer exhibiting the property of recognizing 9,10-diphenylanthracene

Abstract: Efficient chromatography-free synthesis of a new example of an aromatic dendrimer bearing nine ferrocene residues and its application in the detection of 9,10-diphenylanthracene are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
1
1
0
Order By: Relevance
“…It is noteworthy that our previous studies ( 1 H NMR, 1 H DOSY NMR, cold‐spray ESI‐MS and emission spectra experiments) revealed that Fc‐1 can interact with aromatic species by means of dynamic π‐π stacking‐like non‐covalent forces [35] . This observation was further supported by our works on 1,3,5‐triphenylbenzene containing dendritic molecule [46] . Furthermore, our studies on the interactions between Fc‐2 and pyrene as the representative aromatic molecule revealed that this interaction can be characterized by the similar apparent association constant ( K app ) value as for the pyrene‐ Fc‐1 system reported previously; [35] The estimated K app value for pyrene‐ Fc‐2 system equals to 5.1(2) ⋅ 10 2 M −1 (Gibbs free energy (Δ G ) value is −15.5 kJ ⋅ mol −1 ; see data and calculation details in Section S6, Supporting Information).…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…It is noteworthy that our previous studies ( 1 H NMR, 1 H DOSY NMR, cold‐spray ESI‐MS and emission spectra experiments) revealed that Fc‐1 can interact with aromatic species by means of dynamic π‐π stacking‐like non‐covalent forces [35] . This observation was further supported by our works on 1,3,5‐triphenylbenzene containing dendritic molecule [46] . Furthermore, our studies on the interactions between Fc‐2 and pyrene as the representative aromatic molecule revealed that this interaction can be characterized by the similar apparent association constant ( K app ) value as for the pyrene‐ Fc‐1 system reported previously; [35] The estimated K app value for pyrene‐ Fc‐2 system equals to 5.1(2) ⋅ 10 2 M −1 (Gibbs free energy (Δ G ) value is −15.5 kJ ⋅ mol −1 ; see data and calculation details in Section S6, Supporting Information).…”
Section: Resultssupporting
confidence: 74%
“…[35] This observation was further supported by our works on 1,3,5triphenylbenzene containing dendritic molecule. [46] Furthermore, our studies on the interactions between Fc-2 and pyrene as the representative aromatic molecule revealed that this interaction can be characterized by the similar apparent association constant (K app ) value as for the pyrene-Fc-1 system reported previously; [35] The estimated K app value for pyrene-Fc-2 system equals to 5.1(2) • 10 2 M À 1 (Gibbs free energy (ΔG) value is À 15.5 kJ • mol À 1 ; see data and calculation details in Section S6, Supporting Information). For comparison, for the pyrene-Fc-1 system, K app and ΔG equal to 4.0(3) • 10 2 M À 1 and À 14.9 kJ • mol À 1 , respectively.…”
Section: Resultsmentioning
confidence: 99%